Oscillatory Behaviors of microRNA Networks: Emerging Roles in Retinal Development - Fishman, Elizabeth S.; Han, Jisoo S.; La Torre, Anna (Frontiers in Cell and Developmental Biology, 2022)
A broad repertoire of transcription factors and other genes display oscillatory patterns of expression, typically ranging from 30 minutes to 24 hours. These oscillations are associated with a variety of biological processes, including the circadian cycle, somite segmentation, cell cycle, and metabolism. These rhythmic behaviors are often prompted by transcriptional feedback loops in which transcriptional activities are inhibited by their corresponding gene target products. Oscillatory transcriptional patterns have been proposed as a mechanism to drive biological clocks, the molecular machinery that transforms temporal information into accurate spatial patterning during development. Notably, several microRNAs (miRNAs) -small non-coding RNA molecules- have been recently shown to both exhibit rhythmic expression patterns and regulate oscillatory activities. Here, we discuss some of these new findings in the context of the developing retina. We propose that miRNA oscillations are a powerful mechanism to coordinate signaling pathways and gene expression, and that addressing the dynamic interplay between miRNA expression and their target genes could be key for a more complete understanding of many developmental processes.